Neuroinflammation in Huntington's disease : Causes, consequences, and treatment strategies - Blusch, Alina; Björkqvist, Maria ; 0000-0001-8550-0431 (Journal of Huntington's disease, 2025)
Huntington's disease (HD) is a progressive neurodegenerative disorder, and increasing evidence suggests that inflammation, both central and peripheral, plays a role in disease progression. Neurohistology and neuroimaging studies illustrate neuroinflammatory processes as part of HD pathophysiology. Furthermore, studies of blood and cerebrospinal fluid from HD patients show altered levels of inflammatory markers and immune cell populations that could influence neuroinflammation and the neurodegenerative process. Here, we review findings contributing to our understanding of the significance of immune activation in HD pathology. We discuss evidence of intrinsic effects of mutant huntingtin within immune cells and central immune alterations that contribute to neuroinflammation and neurodegeneration. We address the roles of central immune cells, as well as the potential contributions of peripheral signals and cell types in HD immune activation. We further discuss opportunities and challenges in utilizing immune-modulation strategies for future treatment approaches. A better understanding of neuroimmune interactions in HD can provide insights for manipulating these responses, potentially facilitating the development of therapies aimed at reducing the impact of neuroinflammatory and degenerative processes.
Keywords: Huntington's disease; immune cells; immune system; inflammation; neuroinflammation; treatment strategies